(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This article scientifically and theoretically examines the national upbringing traditions formed in the Uzbek family and their impact on the spiritual, moral and social development of the child’s personality. During the study, values, traditions and the personal example of parents as important factors in raising a child in the family were analyzed. Special attention is also paid to the relevance of national upbringing in the context of globalization and its integration with modern pedagogical approaches.